Gender and Transport in MENA : Case Studies from West Bank Gaza and Yemen - Aljounaidi, Lamis (World Bank, Washington, DC, 2012)
Mobility is a major factor in access to economic resources, education, health, and other key elements influencing women's empowerment. In Middle East and North African countries, like in many other developing economies, women's mobility is constrained not only by limited transport supply, but also by social factors reducing women's access to the outside world as well as political realities. The brief is a summary of three studies that were implemented on gender and transport in the region, two in Yemen and one in West Bank Gaza. The goal was to better understand how transport infrastructure and services are facilitating or constraining women's access to resources, markets, training, information, and employment. A key objective was also to identify priority areas for public intervention to improve women's mobility and enhance their access to economic empowerment.